Physical health of adults with intellectual disabilities - Prasher, Vee P.; Janicki, Matthew P., 1943-; Wiley InterScience (Online service) (Oxford ; Malden, MA : Blackwell Pub., 2002)
This book is the second in a series with the International Association for the Scientific Study of Intellectual Disabilities (Series Editor: Matthew P. Janicki). These publications are designed to address the issues of health, adult development and aging among persons with intellectual disabilities. Physical health considerations of persons with an intellectual disability are attracting attention within the contexts of human rights, public health, and health promotion. Research has shown that the prevalence of certain conditions and diseases is much higher in adults with an intellectual disabi.
Contents -- Preface -- 1 Epidemiological Issues -- 2 Assessing Physical Health -- 3 Physical Health and Clinical Phenotypes -- 4 Cerebral Palsy -- 5 Visual Impairment -- 6 Hearing Impairment -- 7 Epilepsy -- 8 Endocrinological Issues -- 9 Dentition and Oral Health -- 10 Nutrition and Physical Health -- 11 Health Promotion and Disease Prevention -- 12 Barriers to Health Care Services and the Role of the Physician -- 13 Future Prospects: A Challenge to Promote Wellness -- Appendix -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Health promotion; Developmentally disabled -- Health and hygiene; Mentally Disabled Persons; Health Promotion; Health Status; HEALTH & FITNESS -- Physical Impairments; Developmentally disabled -- Health and hygiene; Health promotion; Health promotion. -- Mentally Disabled Persons; Electronic books; Electronic books